BACKGROUND OF THE ANATOMY OF PERITONEAL CARCINOMATOSIS. ANALYSIS OF LITERATURE AND SHAREHOLDERS DATA - R. Sh. Ishmuratova; Sh. R. Kzyrgalin; K. Sh. Gantsev; R. S. Minigazimov; S. V. Solomenny; L. V. Khalikova (Креативная хирургия и онкология, 2017)
In the article the anatomical features of the peritoneum structure have been described in accordance with  the  medical  records  supplemented by the  author’s  illustrations.  The functional differences of various peritoneum areas are shown  based  on its structure. Also, issues  relating  to  the  anatomical features of  the  peritoneum such  as «hatches» and  its influence on the development of peritoneal carcinomatosis have been touched upon.